Controlling the lithium proton exchange of LLZO to enable reproducible processing and performance optimization. Issue 8 (28th January 2021) - Rosen, Melanie; Ye, Ruijie; Mann, Markus; Lobe, Sandra; Finsterbusch, Martin; Guillon, Olivier; Fattakhova-Rohlfing, Dina
Abstract : A new, mechanistic understanding of the lithium proton exchange in LLZO enables reproducible processing and performance optimization for tape-cast components. Abstract : Ceramic solid state-electrolytes attract significant attention due to their intrinsic safety and, in the case of the garnet type Li6.45 Al0.05 La3 Zr1.6 Ta0.4 O12 (LLZO), the possibility to use Li-metal anodes to provide high energy densities on a cell and battery level. However, one of the major obstacles hindering their wide-spread application is the translation and optimization of production processes from laboratory to industrial scale. Even though the plausibility of manufacturing components and cells via wet processing routes like tape casting and screen printing has been shown, the impact of the sensitivity of LLZO to air and protic solvents due to Li + /H + -exchange is not fully understood yet. An uncontrolled alteration of the powder surface results in poorly reproducible processing characteristics and electrochemical performance of the final battery components and full cells. This knowledge gap is the cause of the large performance variations reported across different research labs worldwide and is unacceptable for up-scaling to industrial level. To close this gap, the influence of the Li + /H + -exchange taking place at various steps in the manufacturing process was systematically investigated in this study. For the first time, this allowed a mechanistic understanding of its impact on the processability itself and on the resulting electrochemical performance of a free-standing LLZO separator. The importance of a close control of the pre-treatment and storage conditions of LLZO, as well as contact time with the solvent could be extracted for each step of the manufacturing process. As a result, we were able to optimize the processing of thin, dense, free standing LLZO separators and significantly improve the total Li-ion conductivity to 3.90 × 10 −4 S cm −1 and the critical current density to over 300 μA cm −2 without making structural changes to separator or the starting material. These findings do not only enable a deeper understanding and control over the manufacturing process, but also show potential for further improvement of cell concepts already existing in literature.